Embodied Feeling and Reason in Decision-Making: Assessing the Somatic-Marker Hypothesis - Warren TenHouten (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
Whether or not reason and affect are complementary depends on the task at hand. In ordinary circumstances, problemsolving and decision-making involve both somatic feelings and limbic-structure-based emotions. Feelings, experienced as states of the body, can contribute to decision-making by triggering heuristic cues and rapidly eliminating negative behavioral alternatives, in part by providing what Damasio call somatic markers (Damasio, Tranel and Damasio, 1991; Damasio, 1994, 1999, 2003). However, if task-performance is motivated by potentially large rewards, with high demands on short-term memory and on concentration, the dorsolateral prefrontal cortexcan inhibit affects manifested in the medial prefrontal cortex in order to carry out the necessary cognitive operations. We interpret these two different mental task situations using dual process models. Although experimental evidence from studies of normal subjects and frontal-lobe-damaged patients performing the Iowa Gambling Task has been interpreted as supportive of the somatic-marker hypothesis (SMH), we show that this evidence has been called into question due to faulty study designs. However, studies of normal and psychopathic subjects playing the ultimatum game show that pulse-rate deceleration occurring during the brief period preceding decision-making constitutes a somatic marker. Compared to normal controls, psychopaths show less somatic (electro dermal) activity and act with cool, economic rationality, accepting unfair (<50/50) offers that normal subjects reject on the basis of non-economic values of fairness. The somatic-marker hypothesis is discussed and criticized, and various theories based on this hypothesis are identified.